(untitled) (Journal of Nepal Geological Society, 2017)
A leaf of Dipterocarpus (Dipterocarpaceae) is described from the Lower member of Middle Siwalik of eastern Nepal. Its presence indicates that during the deposition of the sediments there was a warm and humid climate with dry season of not more than 3–4 months. The modern distribution of the genus and family reveals that nowadays they have disappeared from the modern flora of Nepal. The most plausible reason for their disappearance might be an increase in length of the dry season caused by the upliftment of the Himalaya.